Lipid Mediators and Human Leukemic Blasts - Fiancette, Rémi (Hindawi Publishing Corporation, 2011)
Some of the most potent inflammatory mediators share a lipid origin. They regulate a wide spectrum of cellular processes including cell proliferation and apoptosis. However, the precise roles and ways (if any) in which these compounds impact the growth and apoptosis of leukemic blasts remain incompletely resolved. In spite of this, significant advances have been recently made. Here we briefly review the current knowledge about the production of lipid mediators (prostaglandins, leukotrienes, platelet-activating factor) by leukemic blasts, the enzymatic activities (phospholipase A(2), cyclooxygenases, lipoxygenases) involved in their productions and their effects (through specific membrane bound receptors) on the growth, and apoptosis of leukemic blasts.